FAKTOR – FAKTOR YANG MEMPENGARUH MANAJEMEN ASSET PADA PEMERINTAH KOTA LHOKSEUMAWE - Yusnidar Yusnidar; Muammar Khadafi; Damanhur Damanhu (J-MIND (Jurnal Manajemen Indonesia), 2021)
ABSTRACT This study aims to examine the Factors Affecting Asset Management in Lhokseumawe City Government. The data used in this study are primary data of 102 respondents. Data analysis method in this research uses structural equation model with the help of analysis of moment structure. The results showed that, regional apparatus, regulations, accounting information systems and organizational commitment had a positive and significant effect on asset management in the Lhokseumawe City Government. While accountability does not affect asset management in the Lhokseumawe City Government. Keywords:Quality of Regional Apparatus, Regulation, Accountability, Accounting Information Systems, Organizational Commitment and Asset Management